2021
DOI: 10.1186/s12865-021-00407-x
|View full text |Cite
|
Sign up to set email alerts
|

Activin a suppresses peripheral CD8+ T lymphocyte activity in acute-phase Kawasaki disease

Abstract: Background Kawasaki disease is an autoimmune disease characterized by systemic vasculitis of unknown aetiology and most commonly occurs in children under 5 years old. Previous studies have found that the over-activation of lymphocytes is an important mechanism of Kawasaki disease. Activin A, also known as immunosuppressive factor P, is a multifunctional growth and transforming factor. However, whether activin A is involved in the regulation of peripheral lymphocytes activity in Kawasaki disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…These data is in agreement with a previous study that described a significant T lymphopenia (in our case we found also a significant reduction of B lymphocytes) during the acute phase of MIS-C with the subsequent reversion during resolution, again similarly to what we observed in adult patients with severe COVID, that had a significant B and T cell lymphopenia [ 12 ] reverted after one week of hospitalization [ 13 ]. While, differently from our results, a previous study described the alteration of cytotoxic lymphocytes in KD [ 16 ] and another reported a suppression of peripheral activity but not a reduction of the number of CD8 in 7 patients with KD [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These data is in agreement with a previous study that described a significant T lymphopenia (in our case we found also a significant reduction of B lymphocytes) during the acute phase of MIS-C with the subsequent reversion during resolution, again similarly to what we observed in adult patients with severe COVID, that had a significant B and T cell lymphopenia [ 12 ] reverted after one week of hospitalization [ 13 ]. While, differently from our results, a previous study described the alteration of cytotoxic lymphocytes in KD [ 16 ] and another reported a suppression of peripheral activity but not a reduction of the number of CD8 in 7 patients with KD [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The deep immune profiling of patients with MIS-C demonstrated a marked, although transient, lymphopenia with a more pronounced T-cell involvement i.e., the same profile that we observed in adult patients with severe, acute Sars-CoV-2 infection [ 12 , 13 ]. Furthermore, a suppression of CD8 was reported in KD [ 14 ]. The circulating cell profile of patients with the two diseases helps to define diagnostic biomarkers that may contribute to the early diagnosis of each of the two entities and also to discriminate between them [ 15 ] since different outcome and therapy response were reported in patients with KD and MIS-C [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to TGF-β blockade, knockdown (KD) of activin A induced CD8 + T cells priming during radiation therapy of 4T1 tumor-bearing mice, and combination of TGF-β blockade with acitivin A KD significantly augmented this effect ( 55 , 56 ). Activin A could also inhibit the activity of CD8 + T cells in peripheral blood of acute Kawasaki disease patients ( 57 ).…”
Section: Activin a Regulation Of The Adaptive Immune Systemmentioning
confidence: 99%